Acute effects of high-definition transcranial direct current stimulation on dynamic postural stability in a y-balance task - Wang, B.; Xiao, S.; Shen, B.; Yu, C.; Fu, W. (ISBS Proceedings Archive (Michigan), 2022)
Purpose: The present study aimed to investigate whether anodal transcranial direct current stimulation (a-tDCS) of the primary motor cortex (M1) could affect dynamic postural stability in healthy young adults. Methods: A randomized, crossover, double-blind experimental design was used in this study. Effects of tDCS on dynamic postural stability were assessed baseline and immediately after tDCS. Results: a-tDCS of M1 significantly decreased the COP of medial-lateral displacement on the posteromedial and posterolateral direction, and path length on the posteromedial direction in the Y-balance, while no significant changes in the sham tDCS (s-tDCS) condition. Conclusion: This study provided evidence that a-tDCS enhanced dynamic postural stability in healthy young adults.